Digital Literacy, Skills, and Security: Impact on Digital Leadership in Higher Education - Pranata, Sungguh Ponten (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research examines the influence of digital literacy and social media usage skills on digital leadership in higher education and the moderating role of digital security and antivirus software. This research uses the path analysis method with Smart PLS 4.0 software. They were conducted from January to February 2024, involving 100 management program students using the saturated sampling method. The research results show that digital literacy and social media usage skills positively and significantly affect digital leadership. Digital security also has a positive impact on digital leadership. However, the hypothesis regarding antivirus and security systems as moderating variables was rejected, indicating that they did not increase the influence of digital security or social media skills on digital leadership. This research contributes to developing university curricula and leadership programs by integrating aspects of digital security. The model successfully identified significant influences on digital leadership with high reliability and validity. The rejection of some moderation hypotheses suggests that further research is needed to understand the dynamics between these variables, paving the way for refining the model and exploring other influencing factors.